Comparison of arthroscopic and open reduction of conservatively irreducible dislocated hips of children. (1st August 2019) - Presch, C.; Eberhardt, O.; Wirth, T.; Fernandez, F. F.
Abstract: Purpose: Children with sonographic grade IV hip dysplasia according to Graf and with failed conservative treatment usually need surgical reduction afterwards. Surgical reduction of the hip can lead to severe complications, the occurrence of residual acetabular dysplasia, osteonecrosis, redislocation and other postoperative complications. This paper investigates whether arthroscopic reduction is a promising alternative to open reduction. Methods: We retrospectively examined 66 patients (78 hips) who were not older than two years at the first time of surgery. Arthroscopic reduction was performed on 17 children (19 hips) and open reduction on 49 children (59 hips). Patient records were used to determine redislocation, postoperative complication and residual dysplasia. Radiographs were used to determine Tönnis classification for osteonecrosis and pathological acetabular (AC) angle for residual dysplasia. We considered data up to a two-year follow-up. Statistical evaluation was performed with binary logistic regression. Results: After arthroscopic reduction, 6% showed osteonecrosis, compared with 20% with open reduction (p = 0.334). Redislocation was not observed after arthroscopic reduction but for 29% after open reduction (p = 0.005). An improvement of femoral head coverage was achieved with residual dysplasia of 23.5% after arthroscopic reduction, compared with 62% after open reduction (p = 0.002). Conclusion: The arthroscopic procedure represents a meaningful alternative to the open procedure due to a lower complication rate, a safe setting, a lower rate of residual dysplasia, no observed redislocation and occurrence of osteonecrosis only once in the arthroscopic group of developmental dysplasia of the hip. The arthroscopic procedure should be tested in further studies and in other clinics in order to broaden the empirical base. Level of Evidence: Level III (retrospective cohort study)